Exploring the Linguistic Landscape of Public Elementary Schools in Medan: Understanding Forms and Functions - Gapur, Abdul; Taulia; Wardana, Muhammad Kiki (International Journal of Culture and Art Studies, 2024)
The linguistic landscape, or "schoolscape," in public elementary schools in Medan, Indonesia, is a relatively new area of study in linguistics. This descriptive qualitative research explores language use within the school environment, considering its social and cultural aspects. The study aims to analyze the linguistic forms, usage, and functions present in the linguistic landscape of these schools. Data from photographs capturing linguistic units was collected from four public elementary schools in Medan. This study employed systematic sampling, specifically purposive sampling, to select public elementary schools in Medan based on criteria related to the city's main areas with diverse linguistic units. The findings reveal various linguistic forms, including acronyms, words, phrases, sentences, and monolingual and bilingual texts. Language within the linguistic landscape serves informational and symbolic functions, providing information to readers and reflecting the relationship between language and power through linguistic signs associated with local leaders. While Indonesian is the dominant language used, there is a lack of representation of specific ethnic or cultural identities. The findings have global implications, revealing language's role in education and its impact on social and cultural dynamics. Understanding linguistic forms, usage, and functions provides valuable insights for education policies promoting language diversity, skills, and cultural inclusivity. The study suggests enriching the linguistic landscape by considering the use of local or minority languages existing in the region. This study contributes to understanding linguistic landscapes in Indonesian schools and highlights the importance of incorporating diverse languages to promote language proficiency and cultural preservation.